2020
DOI: 10.26522/brocked.v29i2.835
|View full text |Cite
|
Sign up to set email alerts
|

E3Cs: A Research-Based Model for Effective Digital Learning for K-6 Schools

Abstract: Due to the COVID-19 pandemic, teachers in Ontario were thrust into a new teaching situation at the end of the 20192020 school year for which few were prepared. To address the need for guidance in transitioning to distance teaching, we offer the e-3Cs model, a research-based framework with flexible elements essential for promoting optimum distance interactions for K12 learning, more specifically applied to younger learners (K6). Serving as a tool for designing age-appropriate digital instruction while honour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…One participant describes this as due in part to students' not turning on their cameras during Zoom calls, while others highlighted the inauthenticity of Zoom environments as well as difficulties in offering individualized support and "creating class community." A recent study by Figg et al (2020) addressed similar challenges voiced by Ontario K-6 teachers inquiring about best practices for digital learning. The study responded to various difficulties reported by teachers such as low student engagement, lack of accountability, and a lower quality of student work online due, in part, to teacher unpreparedness and poor support: "Instructors felt frustrated with their own teaching performances and were overwhelmed by the abundance of electronic tools.…”
Section: What Issues and Concerns Are Tcs And Their Students Facing W...mentioning
confidence: 96%
“…One participant describes this as due in part to students' not turning on their cameras during Zoom calls, while others highlighted the inauthenticity of Zoom environments as well as difficulties in offering individualized support and "creating class community." A recent study by Figg et al (2020) addressed similar challenges voiced by Ontario K-6 teachers inquiring about best practices for digital learning. The study responded to various difficulties reported by teachers such as low student engagement, lack of accountability, and a lower quality of student work online due, in part, to teacher unpreparedness and poor support: "Instructors felt frustrated with their own teaching performances and were overwhelmed by the abundance of electronic tools.…”
Section: What Issues and Concerns Are Tcs And Their Students Facing W...mentioning
confidence: 96%